PERBANDINGAN SANKSI PIDANA PELAKU SEKS BEBAS DALAM QANUN ACEH DAN KUHP INDONESIA - Latif, H. Jalil; had, Abunawas (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2024)
The study was intended to analyze the existence of criminal sanctions against premarital sex in a legal perspective on qanun in aceh and Indonesia's positive laws. Premarital sex is sexual behavior outside the bonds of marriage that conflict with religious values and social norms. Premarital sex offenders can be punished on the basis of qanun's laws in aceh and Indonesia's positive laws. The study uses normative research methods by analyzing qanun aceh resources and Indonesia's positive laws relating to criminal sanctions against premarital sex. Criminal penalties used in qanun's law in aceh involve a maximum flogging of 100 times. On the other hand, Indonesia's positive laws also set out criminal penalties against sexually promiscuous people. However, there is an approach between qanun's law in aceh and Indonesia's positive laws on premarital sex management. Qanun aceh focuses more on aspects of religion and morals, while in the context of Indonesia's positive laws which have a diversity of religion and culture, the implementation of criminal sanctions against sexually premarital sex should also be concerned about the principle of justice and religious freedom.